Tapping into the environmental co-benefits of improved tropical forages for an agroecological transformation of livestock production systems - Notenbaert, An Maria Omer; Douxchamps, Sabine; Villegas, Daniel Mauricio; Arango, Jacobo; Paul, Birthe K.; Burkart, Stefan; Rao, Idupulapati M.; Kettle, Christopher J.; Rudel, Thomas; Vásquez, Eduardo; Teutscherova, Nikola; Chirinda, Ngonidzashe; et al. (Frontiers Media, 2021)
Livestock are critical for incomes, livelihoods, nutrition and ecosystems management throughout the global South. Livestock production and the consumption of livestock-based foods such as meat, cheese, and milk is, however, under global scrutiny for its contribution to global warming, deforestation, biodiversity loss, water use, pollution, and land/soil degradation. This paper argues that, although the environmental footprint of livestock production presents a real threat to planetary sustainability, also in the global south, this is highly contextual. Under certain context-specific management regimes livestock can deliver multiple benefits for people and planet. We provide evidence that a move toward sustainable intensification of livestock production is possible and could mitigate negative environmental impacts and even provide critical ecosystem services, such as improved soil health, carbon sequestration, and enhanced biodiversity on farms. The use of cultivated forages, many improved through selection or breeding and including grasses, legumes and trees, in integrated crop-tree-livestock systems is proposed as a stepping stone toward agroecological transformation. We introduce cultivated forages, explain their multi-functionality and provide an overview of where and to what extent the forages have been applied and how this has benefited people and the planet alike. We then examine their potential to contribute to the 13 principles of agroecology and find that integrating cultivated forages in mixed crop-tree-livestock systems follows a wide range of agroecological principles and increases the sustainability of livestock production across the globe. More research is, however, needed at the food system scale to fully understand the role of forages in the sociological and process aspects of agroecology. We make the case for further genetic improvement of cultivated forages and strong multi-disciplinary systems research to strengthen our understanding of the multidimensional impacts of forages and for managing agro-environmental trade-offs. We finish with a call for action, for the agroecological and livestock research and development communities to improve communication and join hands for a sustainable agri-food system transformation.